Daily field checking list by Walter Rosene, May 15, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Paul Clausen, May 15, 1941. Also notes young Red-shouldered Hawks moving around in a nest. Plustek--flatbed